Risk factors for puncture-related complications after cerebrovascular angiography and neuroendovascular intervention with distal transradial approach - Weikai Wang; Yonggang Ma; Chao Wang; Peng Shi; Weibo Lv; Guangliang Fan; Chao Sun (BMC Neurology)
Abstract Background and purpose To determine the risk factors for puncture-related complications after the distal transradial approach (dTRA) for cerebrovascular angiography and neuroendovascular intervention and to explore the incidence and potential mechanisms of procedural failure and puncture-related complications. Materials and methods From February to November 2023, 62 patients underwent dTRA in our department. Demographic, clinical, and procedural data were collected retrospectively. Postoperative puncture-related complications were defined as a syndrome of major hematoma, minor hematoma, arterial spasm/occlusion, arteriovenous fistula, pseudoaneurysm, and neuropathy. Univariate and multivariate logistic regressions were performed to identify significant factors contributing to puncture-related complications. Results Forty-five diagnostic cerebral angiograms and 17 neurointerventions were performed or attempted with dTRA in 62 patients. Procedural success was achieved via dTRA in 47 (75.8%) patients, whereas 15 (24.2%) required conversion to other approaches. Reasons for failure included puncture failure (n = 8), inability to cannulate due to arterial spasm (n = 6), and inadequate catheter support of the left vertebral artery (n = 1). 17.0% (8/47) of patients had postoperative puncture-related complications. Minor hematoma occurred in 8.5% (4/47) of patients, arterial spasm/occlusion in 6.3% (3/47), and neuropathy in 2.1% (1/47). No major complications were observed. On stepwise multivariable regression analysis, BMI (OR = 0.70, 95%CI 0.513 to 0.958; p = 0.026) was an independent risk factor for puncture-related complications, with a cut-off of 24.8 kg/m2 (sensitivity 66.7% and specificity 87.5%). Conclusion Our cohort is the first study of risk factors for puncture-related complications after neurointerventional interventions with dTRA. This study has shown that a low BMI (< 24.8 kg/m2) is independently associated with the development of puncture-related complications.